Pengembangan Komunikasi Pariwisata Lokal dalam Mendukung Branding Pariwisata Nasional "Sapta Pesona” - Pangestu, Panji; Alfatih, Andy; Murti, Krisna; Effendi, Sofyan; Izzudin, Muhammad (geoedusains: Jurnal Pendidikan Geografi, 2023)
This study aims to provide an overview of the Lahat District tourism office's communication strategy in socializing Sapta Pesona to the Tourism Awareness Group. The research was conducted using qualitative methods with a qualitative descriptive approach. Data collection was obtained through field observations, direct interview techniques with parties considered relevant to the research and using data from various authorship literature such as articles, journals and previous research which were then analyzed using analytical techniques from Hubermas and Saldana (2014) and Dimensional Theory. Recognizing Communication Goals from Onong Uchjana Effendy. The research findings show that there are four dimensions in identifying communication targets, namely: 1) Recognizing communication targets with several indicators of the accuracy of communication targets, communication skills in receiving messages. 2) Selection of media as easy access by considering the affordability of costs. 3). Assessment of the purpose of communication messages by understanding the clarity of the message, the ease of the message to be understood, the completeness of the message content and the accuracy of the delivery technique. 4) The role of a communicator who has appeal and credibility.